Komplikace operační léčby zlomenin proximálního femuru metodou DHS - Hrubina, M; Skoták, M; Běhounek, J (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2010)
PURPOSE OF THE STUDY: To present the results of Dynamic Hip Screw (DHS) osteosynthesis for the treatment of proximal femoral fractures with a focus on specific complications of this method. MATERIAL From 1997 till 2007, the authors performed 367 DHS osteosyntheses to treat 341 patients with fractures of the proximal femur. The average patient age was 81.8 years (21-101). Twenty-six patients had surgery for bilateral fractures. METHODS: Osteosynthesis was always carried out using a 135° DHS (Medin, Nové Město na Moravě, Czech Republic) to manage fractures of the femoral neck (13 ); trochanteric and basic cervical fractures (349 ) and subtrochanteric fractures (5). At the end of 2009 the group was evaluated in terms of specific complications, i.e., intra-operative, early and late post-operative complications, and reoperation incidence. Hip radiographs were made before the patient was discharged, at 6 weeks, then at 3, 6 and 12 months post-operatively.When there were no complications, X-ray examination was repeated every 12 months. RESULTS: A total of 39 specific complications of the DHS system (11 %) were recorded. The 17 intra-operative complications included: insufficient reduction (10), broken tip of a K-wire (3), faulty technical procedure (2) and fracture of the distal fragment during surgery (2). In addition, 22 post-operative complications (both early and late) were recorded: "cut-out" phenomenon (6), avascular necrosis of the femoral head (5), progression of coxarthrosis (4), screw breakage (2) , femoral fracture under the plate (2), pseudoarthrosis (2) and late infection (1). Complications in relation to the fracture site were as follows: femoral neck fractures, 3/13 (23 %) all requiring revision surgery; trochanteric fractures, 35/349 (10 %), of these 12 reoperated; subtrochanteric factures, 1/5 (20 %) no revision surgery required. Of the 367 fractures treated by DHS osteosynthesis, 15 (4 %) required revision surgery for specific complications. The mortality rate within one year of surgery was 49 %. DISCUSSION: Enough information on treatment options for proximal femoral fractures can be found in the literature. However, less attention is paid to their complications. The authors used DHS osteosynthesis to treat 367 fractures during 11 years, and recorded 11 % of complications. These can be prevented by the correct indication (the final decision of the implant to be used is sometimes made only after a fracture reduction under an X-ray image intensifier on the operating theatre), correctly performed procedure and thorough post-operative care. The high one-year mortality was due to the high average age in the group. CONCLUSIONS: The authors regard DHS as an effective method to treat stable pertrochanteric fractures and fractures of the femoral neck in younger patients. Complications most often occur as a result of technical mistakes made by surgeons.
Keywords: Male; lidé středního věku; vnitřní fixace fraktury; senioři nad 80 let; Aged, 80 and over; fraktury krčku femuru; Radiography; Humans; Middle Aged; senioři; kostní šrouby; mužské pohlaví; Female; fraktury kyčle; Aged; ženské pohlaví; Hip Fractures; Femoral Neck Fractures; mladý dospělý; Adult; Young Adult; Bone Screws; Fracture Fixation, Internal; dospělí; lidé; radiografie